Perbandingan Daya Dukung Ultimit Tiang Pancang Antara Metode Teoretis Dan Metode Aktual Dengan Konfigurasi Tiang Dan Kedalaman - Muhammad Suhaimi; Fathurrozi Fathurrozi; Muhammad Aspihani Rahman (P3M Politeknik Negeri Banjarmasin, 2017)
The soil layers in Banjarmasin are generally soft clay soil, whereas hard soil layers are in the range of 30 to 50 matters below ground level. Therefore, deep foundation is the right alternative to build a stronger and more stable construction. This study aims to determine the comparison value of pile bearing capacity based on theoretical and actual result so it can be used to determine the selection for planning and execution in installation of piles foundation. The study was conducted at Lambung Mangkurat University (ULM) Campus, Jl. Brigjend H. Hasan Kayu Tangi, Banjarmasin. This study used mini piles size of 20cm x 20cm with vary in length. The type of soil bearing capacity against piles is friction. In theoretical calculation, it used sondir data while in actual bearing capacity it used the result from loading data test at pile B, E, G and I, then all data processed and analyzed by using methods from Davission (1973), Mazurkiewich (1973), and Chin (1970). The results of the calculation of bearing capacity of the ultimit piles, both theoretical and actual show a very significant difference. A very large difference on pile E4 with a depth of 12 meters of 53,25%, and the smallest difference in pile I with a depth of 12 meters by 15,25%.